Analisis Gambar Ilustrasi Busana Mahasiswa Akademi Kesejahteraan Sosial AKK Yogyakarta Tinjauan Aspek proporsi Anatomi Manusia - Danu widiantoro (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2020)
This research aims to analyse the drawings of fashion illustrations by the students of AKS-AKK Yogyakarta about the proportion of human anatomy. This is important because the students of the fashion studies Program AKS-AKK Yogyakarta is a prospective practitioner in the field of fashion industry that must possess supporting skills related to the field he has. One such skill is to take a picture of fashion illustration. With the descriptive research method, conducted in this study is to make a description of the illustration of the artwork in conjunction with the proportion of its human anatomy in general, namely the proportion of the body, the proportion of facial anatomy, the proportion of hand anatomy and the proportion of foot anatomy From the results of the analysis of the existing fashion illustration, it can be conveyed that the average understanding of the body's height proportion and the proportion of facial anatomy to the human model is good enough. A slight drawback is on understanding the details of the anatomy proportions of hands and feet. With the findings of advantages and disadvantages on the object of this illustration, it can be a useful input for the development of education in the Program of Tata clothing-AKK Yogyakarta especially about material related to fashion illustration..